The local environment as an object for the study and application of geo–environmental knowledge. a practical experience in colonia del sacramento, uruguay (2009)
This paper intends to account for the importance of methods for significative learning, for the teaching of geography itself and for the prevention and assistance of concrete socioenvironmental problems. For this purpose, the analysis of a pedagogic experience developed with high-school students is exposed, regarding the wetlands system located in Colonia del Sacramento city’s coast strip, in Uruguay. The analysis intends to show how the teaching of geography, with a reflective, critic and active approach, favors the development of cognitive abilities in the learners, which results in the formation of responsible, autonomous and critic individuals, capable of giving solutions and making decisions regarding concrete problems like those mentioned above.